2005
DOI: 10.1175/mwr2930.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Large-Eddy Simulations via Observations of Nocturnal Marine Stratocumulus

Abstract: Data from the first research flight (RF01) of the second Dynamics and Chemistry of Marine Stratocumulus (DYCOMS-II) field study are used to evaluate the fidelity with which large-eddy simulations (LESs) can represent the turbulent structure of stratocumulus-topped boundary layers. The initial data and forcings for this case placed it in an interesting part of parameter space, near the boundary where cloud-top mixing is thought to render the cloud layer unstable on the one hand, or tending toward a decoupled st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

51
815
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 581 publications
(867 citation statements)
references
References 48 publications
51
815
1
Order By: Relevance
“…The ATEX cases are representative of a trade wind cumulus regime in which scattered cumuli rise into a thin, broken stratocumulus layer. The third case (referred to as "DYCOMS-II" hereafter), originally presented in Stevens et al (2005), is an idealized setup based on clouds observed during the second research flight (RF02) of the Second Dynamics and Chemistry of Marine Stratocumulus project (DYCOMS-II) (Stevens et al, 2003). This case is representative of nocturnal marine stratocumulus under conditions of a dry inversion.…”
Section: Model and Methodologymentioning
confidence: 99%
“…The ATEX cases are representative of a trade wind cumulus regime in which scattered cumuli rise into a thin, broken stratocumulus layer. The third case (referred to as "DYCOMS-II" hereafter), originally presented in Stevens et al (2005), is an idealized setup based on clouds observed during the second research flight (RF02) of the Second Dynamics and Chemistry of Marine Stratocumulus project (DYCOMS-II) (Stevens et al, 2003). This case is representative of nocturnal marine stratocumulus under conditions of a dry inversion.…”
Section: Model and Methodologymentioning
confidence: 99%
“…A survey of LES of stratocumulus by Stevens (2002) showed that entrainment rates diagnosed from LES results can vary by up to a factor of two. This has led Stevens et al (2005) to suggest that the entrainment rate may not only be sensitive to the energy-containing eddies but also to the small-scale (subgrid) eddies which are not explicitly resolved in LES, either directly or indirectly through the impact of the small-scale (subgrid) eddies on the large-scale eddies. Such a situation would be in agreement with the concept of an entrainment interfacial layer: since this layer is thin, its dynamics are likely to be dominated by the smaller eddies.…”
Section: Entrainment In Stratocumulusmentioning
confidence: 99%
“…According to Randall (1980) and Deardorff (1980) an appropriate value to be used in the right hand side of (1) is κ 0 = 0.23. As pointed out by many authors (e.g., Kuo and Schubert, 1988;Moeng, 2000;Stevens et al, 2005;Siems et al, 1990), Eq.…”
Section: Modifications Of the Gfsmentioning
confidence: 95%